Parametric study and energy evaluation of the effect of double glazing on the efficiency of a solar panel - Ahliouati Mohamed; El Otmani Rabie; Kandoussi Khalid; Boutaous M’Hamed (E3S Web of Conferences)
The type of glazing used in the design of solar panels is considered one of the key technical aspects that can have a significant impact on the energy performance of the photovoltaic systems. The present study focuses on clarifying the impact of double-glazing on the efficiency of a photovoltaic module, by evaluating the variation in the thickness of the air space between the two layers of glazing that constitute the examined solar configuration. A comparative analysis of three different air space thicknesses was carried out to determine their effect on energy efficiency. An energy balance incorporating various energy parameters was employed, taking into account the influence of external meteorological parameters. The results demonstrate a significant sensitivity between the thickness of the air space in the double glazing and the electrical performance of the photovoltaic module. An average electrical efficiency of 16:02% is obtained for a thickness of 3 mm, and 15:76% for a thickness of 2 cm. In addition, average operating temperatures reached 39:1°C and 42:4°C for these thicknesses respectively.